Risk management analysis of Kopitiam Singkawang business - Charles Tjan; Setiawan Setiawan; Henderson Henderson; Hardianto Hardianto; Jolin Jolin (Junal Ilmu Manajemen, 2023)
Many people have built various kinds of businesses. Starting from the business of selling household goods to businesses that we often find, namely the culinary business, for example the UMKM Kopitiam Singkawang which has a segmentation of regular customers. In running a business, not all companies or businesses run smoothly. There will always be risks that it finds, both directly and indirectly. Seeing the importance of understanding risk management for MSME businesses in running business operations, the research objective is to apply SWOT analysis which aims to determine the effect and frequency of risk occurrence in managing risk management in Kopitiam Singkawang MSME businesses. The research method uses an approach to obtain information through interviews and observations. Several recommendations for MSME businesses based on the weakness and treats factors from the SWOT analysis show that MSME management can evaluate both in terms of facilities, business place concepts and customer flavors. From the SWOT analysis, it was found that Kopitiam Singkawang MSMEs have the strength and potential to advance and continue to develop well even though they have quite intense competition from other business competitors.